Literacies of design : studies of equity and imagination in engineering and making - Wilson-Lopez, Amy, 1980-; Tucker-Raymond, Eli; Esquinca, Alberto; Mejia, Joel Alejandro, 1985- (Purdue University Press, 2022)
"Though engineering design can tackle the world's most pressing challenges, engineering-related courses and experiences are often alienating, especially to people from minority groups. Literacies Design: Studies of Equity and Imagination in Engineering and Making covers the latest pedagogical theories - as well as case studies and practical tips - to support diverse people in identifying problems and designing solutions through engineering and making. Engineers tackle a range of problems, big and small, from climate change to viral transmission to improved handrails for persons with disabilities. Inclusion and equity efforts include not only preparing the next generation of engineers and makers, but also creating and fostering spaces where youth can express their ideas and bring forth their whole selves. This book offers theories and real-life examples for educators and practitioners at every level, from K-12 through higher education and beyond"--